Can migrants be indigenous?: affirmative action, space, and belonging in the Andaman Islands - Zehmisch, Philipp (Modern Asian studies, 2022)
In India, the contested category of Scheduled Tribes (STs) is enacted in order to socially uplift certain indigenous communities. This article concentrates on analysing the intersection between modes of indigenous self-definition, political assertion, and localized conceptualizations of space and belonging. My ethnographic example from the Andaman Islands focuses on the Ranchis, aboriginal labour migrants from the Chotanagpur plateau in central India. Being classified as STs, both in their homelands and other localities to which they migrated, Ranchi activists seek to accomplish coeval recognition in the Andamans. Their demands to be rewarded for the labourers’ contribution to the islands’ development are complicated by their occupation of non-ancestral lands that were originally inhabited by indigenous hunter-gatherer communities. By narrowing the notion of indigeneity, and hence ST status, down to communities who live on ancestral lands and who are culturally, socially, and economically different to migrant communities, state authorities and activists reject the Ranchis’ demands for affirmative action as Adivasis from but not of the Andamans. Reflecting on the existential relationship between land and people in popular understandings of indigenousness, this article aims to investigate the Ranchis’ claims of being migrants, yet also indigenous, in order to explore alternative possibilities to think through the notion of indigeneity. In so doing, I focus on the Ranchis’ subaltern history of racialized labour migration, their lack of voice within the post-colonial welfare regime, and their striving for autonomy and autarky by applying principles of indigenous knowledge and cosmologies from their homelands to the Andamans.